Method for estimating soft clay type seabed embedment by pipeline movement - Kim, D.K. (CRC Press/Balkema, 2015)
The advanced procedure has been proposed to estimate higher accuracy of embedment of pipes that are installed on soft clay seabed. Numerical simulation has been adopted to investigate dynamic seabed embedment and two steps, i.e., static and dynamic analysis, were performed. In total, four empirical curves were developed to estimate dynamic embedment including dynamic phenomena, i.e., behavior of vessel, environmental condition, and behavior of nonlinear soil. The obtained results were compared with existing methods such as design code or guideline to examine the difference of seabed embedment for existing and advance methods. Once this process was performed for each case, a diagram for estimating seabed embedment was established. The applicability of the proposed method was verified through applied examples. This method will be useful in predicting seabed embedment on soft clay, and the structural behaviors of installed subsea pipelines can be changed by the obtained seabed embedment in association with on-bottom stability, free span, and many others. Â© 2015 Taylor & Francis Group, London.